2021
DOI: 10.3390/cancers14010141
|View full text |Cite
|
Sign up to set email alerts
|

Approaches of the Innate Immune System to Ameliorate Adaptive Immunotherapy for B-Cell Non-Hodgkin Lymphoma in Their Microenvironment

Abstract: A dominant paradigm being developed in immunotherapy for hematologic malignancies is of adaptive immunotherapy that involves chimeric antigen receptor (CAR) T cells and bispecific T-cell engagers. CAR T-cell therapy has yielded results that surpass those of the existing salvage immunochemotherapy for patients with relapsed/refractory diffuse large B-cell lymphoma (DLBCL) after first-line immunochemotherapy, while offering a therapeutic option for patients with follicular lymphoma (FL) and mantle cell lymphoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 196 publications
(251 reference statements)
0
9
0
Order By: Relevance
“…This demonstrates the advantages of glycolysis over OXPHOS in cancer metabolism. Besides, accumulating evidence has revealed that the tumor immune microenvironment (TIME) influences the efficacy of immunotherapy and prognosis of cancer patients ( Karube, 2021 ; Watanabe, 2021 ). Apart from the metabolic function, glycolysis-induced hypoxia and lactate accumulation affect the TIME and the function of immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…This demonstrates the advantages of glycolysis over OXPHOS in cancer metabolism. Besides, accumulating evidence has revealed that the tumor immune microenvironment (TIME) influences the efficacy of immunotherapy and prognosis of cancer patients ( Karube, 2021 ; Watanabe, 2021 ). Apart from the metabolic function, glycolysis-induced hypoxia and lactate accumulation affect the TIME and the function of immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1997 by combination therapy of rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP), the percent of cured patients with diffuse large B-cell lymphoma has reached about 60–65% 47 . CD20 is an adequate target on the cell surface of the B-cells 48 , which could be targeted by mAbs.…”
Section: Discussionmentioning
confidence: 99%
“…IL2RB , which is regarded as a hub gene, might be related to the pathogenesis and prognosis of MCL, as determined by the top-weighted network analysis performed in the GSE93291 dataset ( 6 ). TNFRSF9 and its ligand TNFSF9 were applied to trigger innate immune activation, involving therapies such as chimeric antigen receptor (CAR) T-cells and bispecific T-cell engagers in MCL and other B-cell lymphomas ( 36 ). Therefore, further investigations are needed to examine how the immune checkpoint molecules contribute to the pathogenesis of MCL and evaluate the value of these molecules.…”
Section: Discussionmentioning
confidence: 99%